Re-nourish promoting food circularity against food wastage through a nutri-(re)generative food loss and waste research hub - Fajardo, Sophia Emmanuelle dR.; Simoun T. Ong (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
With the Philippines as an agricultural country, increasing amounts of food loss and waste threaten not only the nation's agricultural sustainability and economy, but also its current state of food security. The disconnect between actors of the food supply chain, exacerbated by trade globalization, leads to gaps in the system that increase food wastage and hinder the transition to food circularity. Furthermore, as there is no one- size-fits-all solution, the need for place-based interventions presents challenges in implementation, especially in areas with limited local data on food loss and waste. As such, there is a need to explore the establishment of facilities that promote collaboration, knowledge-sharing, and capacity-building between stakeholders as well as support local research and development in addressing food loss and waste. The project aims to address this through the design development of a research hub in UP Los Baños guided by the principles of food circularity. The strategical framework for the application of key findings and emerging themes into the design proposal was conceptualized through a review of related literature and precedents as well as site, user, and spatial analyses. By exploring how food circularity can be applied to the development of an architectural design framework for a food loss and waste research hub, the project can contribute to the development of local food loss and waste interventions and serve as a reference for the design framework conceptualization of similar projects.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Agricultural wastes management; Refuse disposal facilities; Refuse and refuse disposal; Food waste Management